2018
DOI: 10.3390/fib6040086
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Recycled Material Sources for Wood-Polypropylene Composites: Effect on Internal Composite Structure, Particle Characteristics and Physico-Mechanical Properties

Abstract: In this study, various wood material sources were used for the manufacture of wood-polymer composites (WPC). The materials were categorised as virgin wood particles (VWP), reprocessed WPC particles (RWP) and recycled thermoset composite particles (RCP) and derived from two virgin wood sources, three-layer particleboards, medium-density fibreboards (MDF) boards, or two different wood/polypropylene composites. All produced wood-polypropylene compounds contained 60% wood material and were manufactured using a co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 63 publications
(100 reference statements)
0
18
0
Order By: Relevance
“…Studies by Bütün et al and Krause et al showed that recovered fibers from fiberboards are a suitable material source for the WPC production. Utilizing fibers from medium-density fiberboards revealed beneficial effects on the produced WPC’s physicomechanical properties [ 4 , 5 ]. However, the change of the physicomechanical properties of a particle or fiber-containing polymer is not only affected by its source, but also significantly depending on the particle size and filling level [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Bütün et al and Krause et al showed that recovered fibers from fiberboards are a suitable material source for the WPC production. Utilizing fibers from medium-density fiberboards revealed beneficial effects on the produced WPC’s physicomechanical properties [ 4 , 5 ]. However, the change of the physicomechanical properties of a particle or fiber-containing polymer is not only affected by its source, but also significantly depending on the particle size and filling level [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wood-polymer composites (WPCs) are a group of materials mainly consisting of a thermoplastic polymer as a matrix, wood as reinforcement, and a minor amount of additives such as lubricants and coupling agent [ 5 ]. Due to the increase in consumer ecological awareness, the WPCs have gained more attention as an alternative to traditional polymeric materials [ 6 , 7 ]. Recycled plastics have been used for the production of WPCs since the 1990s with an expressed increase in the last few years [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recycled plastics have been used for the production of WPCs since the 1990s with an expressed increase in the last few years [ 8 ]. However, nationwide WPCs recycling systems are still missing [ 7 ]. By understanding the properties of the recycled WPCs, the re-processing of WPCs can be adjusted and the relationship between physical and mechanical properties can be used to establish a new circular-economy approach for sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…In case of polypropylene, which is one of the most commonly used thermoplastic polymers in the industry, the most popular fillers are chalk and talc. There are also known examples of using other fillers which constitute industry waste, such as phosphogyp sum [19], eggshells [20], wood flour [21,22] or nutshells [23]. By introducing various types of powder fillers into a polypropylene matrix, the stiffness and hardness can be significantly increased.…”
Section: Właściwości Kompozytów Polipropylenowych Napełnionych Odpadomentioning
confidence: 99%